Inconsequence: Lesbian representation and the logic of sexual sequence - Jagose, Annamarie (Cornell University Press, 2018)
The field of lesbian studies is often framed in terms of the relation between lesbianism and invisibility. Annamarie Jagose here takes a radical new approach, suggesting that the focus on invisibility and visibility is perhaps not the most productive way of looking at lesbian representability. Jagose argues that the theoretical preoccupation with metaphors of visibility is part of the problem it attempts to remedy. In her account, the regulatory difference between heterosexuality and homosexuality relies less on codes of visual recognition than on a cultural adherence to the force of first order, second order sexual sequence. As Jagose points out, sequence does not simply specify what comes before and what comes after; it also implies precedence: what comes first and what comes second. Jagose reads canonical novels by Charles Dickens, Henry James, Virginia Woolf, and Daphne du Maurier, drawing upon their elaboration of sexual sequence. In these innovative readings, tropes such as first and second, origin and outcome, and heterosexuality and homosexuality are shown to reinforce heterosexual precedence. Inconsequence intervenes in current debates in lesbian historiography, taking as its pivotal moment the fin-de-siècle phenomenon of the sexological codification of sexual taxonomies and concluding with a reading of a post-Kinsey pulp sexological text. Throughout, Jagose reminds us that categories of sexual registration are always back-formations, secondary, and belated, not only for those who identify as lesbian but also for all sexual subjects.
Keywords: approches et analyses; arts; discipline; discours dominant; littérature; personnes lesbiennes; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; études littéraires

Peau: à propos de sexe, de classe et de littérature - Allison, Dorothy.. (Cambourakis, 2015)
Activiste féministe lesbienne radicale depuis les années 1970, Dorothy Allison a connu le succès avec ses romans (L’Histoire de Bone, Retour à Cayro). En 1994, elle publie Peau, un recueil d’essais. Elle y parle de son enfance, d’inceste, de lesbophobie. Elle raconte son engagement féministe, sa sexualité, les « Sex Wars » des années 1980. Elle partage ses réflexions sur la littérature : comment écrire l’extrême misère sociale, comment écrire sur le sexe ? Un livre tout à la fois intime, décapant et profondément politique, réédité avec sept textes inédits en français.
Keywords: amériques; approches et analyses; arts; cours; discipline; discours dominant; fem1300; histoire et politique; lesbianisme; militance; personnes lesbiennes; premier cycle; privilèges; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail du sexe; états-unis; études littéraires

La chair décevante - Bernier, Jovette (Biblio Fides, 2014)
Sur l'écran, sous les feux de la rampe, la souffrance est divine pour la foule. La même souffrance dans la rue et dans les chambres closes, cela s'appelle du déshonneur. [...] Il y a quelque chose de plus fort que le courage, la tendresse, le dévouement, le sacrifice; il y a plus fort que toi, l'Amour, et toi, la Mort ; plus fort que tout, plus fort que vous tous, il y a la Vie.
Keywords: 1900-1999; 1920-1929; 1930-1939; amériques; approches et analyses; arts; canada; cours; discipline; lit3495; maternité; patriarcat; point de vue situé; premier cycle; périodes historiques; québec; ressource en ligne; roman; régions géographiques; sexualité; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Sapphic fathers: Discourses of same-sex desire from nineteenth-century France - Schultz, Gretchen (University of Toronto Press, 2014)
Literature that explored female homosexuality flourished in late nineteenth-century France. Poets, novelists, and pornographers, whether Symbolists, Realists, or Decadents, were all part of this literary moment. In Sapphic Fathers, Gretchen Schultz explores how these male writers and their readers took lesbianism as a cipher for apprehensions about sex and gender during a time of social and political upheaval. Tracing this phenomenon through poetry (Baudelaire, Verlaine), erotica and the popular novel (Belot), and literary fiction (Zola, Maupassant, Péladan, Mendès), and into scientific treatises, Schultz demonstrates that the literary discourse on lesbianism became the basis for the scientific and medical understanding of female same-sex desire in France. She also shows that the cumulative impact of this discourse left tangible traces that lasted well beyond nineteenth-century France, persisting into twentieth-century America to become the basis of lesbian pulp fiction after the Second World War.
Keywords: amériques; approches et analyses; arts; discipline; discours dominant; europe; france; histoire et politique; hétérosexisme; patriarcat; personnes lesbiennes; ressource en ligne; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; violences; états-unis; études littéraires

Sex and disability - McRuer, Robert; Mollow, Anna (Duke University Press, 2012)
The title of this collection of essays, Sex and Disability, unites two terms that the popular imagination often regards as incongruous. The major texts in sexuality studies, including queer theory, rarely mention disability, and foundational texts in disability studies do not discuss sex in much detail. What if'sex'and'disability'were understood as intimately related concepts? And what if disabled people were seen as both subjects and objects of a range of erotic desires and practices? These are among the questions that this collection's contributors engage. From multiple perspectives—including literary analysis, ethnography, and autobiography—they consider how sex and disability come together and how disabled people negotiate sex and sexual identities in ableist and heteronormative culture. Queering disability studies, while also expanding the purview of queer and sexuality studies, these essays shake up notions about who and what is sexy and sexualizable, what counts as sex, and what desire is. At the same time, they challenge conceptions of disability in the dominant culture, queer studies, and disability studies.Contributors. Chris Bell, Michael Davidson, Lennard J. Davis, Michel Desjardins, Lezlie Frye, Rachael Groner, Kristen Harmon, Michelle Jarman, Alison Kafer, Riva Lehrer, Nicole Markotić, Robert McRuer, Anna Mollow, Rachel O'Connell, Russell Shuttleworth, David Serlin, Tobin Siebers, Abby L. Wilkerson
Le texte Siebers, T. (2012). A sexual culture for disabled people a été donné à lire au cours sex1920. Le texte Mollow, A. (2012). Is Sex Disability? Queer Theory and the Disability Drive a été donné en lecture au cours SEX1920.
Keywords: approches et analyses; arts; autobiographie; capacitisme; cours; discipline; ethnographie; premier cycle; queer; ressource en ligne; sciences humaines; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

L'identité de genre dans les oeuvres de George Sand et Colette - Krauthaker, Marion (L'Harmattan, 2011)
George Sand et Colette sont connues pour avoir publié des ouvrages dévoilant un grand modernisme et un engagement sur la question des relations entre les sexes. Cet ouvrage dévoile qu'alors que le XIXe et le début du XXe siècle se focalisaient surtout sur des revendications féministes visant la libération des femmes, ces deux auteures cherchaient aussi à dénoncer les codes traditionnellement imposés à tous les individus et à leur identité. Alors que le concept d'identité de genre n'était pas clairement théorisé à l'époque, leurs écrits suggèrent que Sand et Colette avaient déjà l'intuition que les hommes comme les femmes pouvaient être victimes des lois sociales fondées sur la différence sexuelle. Elles dénonçaient les limites que la société imposait aux sujets selon leur sexe et subvertissaient les schémas traditionnels de la formation identitaire. Pour cela, elles présentaient souvent la bipolarité des structures patriarcales comme une construction artificielle, elles mettaient en scène de nouveaux modèles de "féminité", de "masculinité" et de sexualité et elles démontraient une indéniable volonté de rupture et de remise en cause des traditions. Cette étude met aussi en évidence comment ces subversions successives peuvent être lues comme des présentations très modernes d'une identité de genre perçue comme une structure en constante mutation qui désavoue les inscriptions traditionnelles et normalisées. De manière étonnante, les illustrations d'expressions identitaires individuelles et plurielles chez Sand et l'élaboration d'un nouvel ordre des identités chez Colette rapprochent leurs écrits de théorisations contemporaines du genre.
Keywords: approches et analyses; arts; corps; discipline; europe; france; genre; histoire et politique; hétérosexisme; littérature; patriarcat; ressource en ligne; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; études littéraires

Mettre l'amitié au premier plan : passés et futurs féministes - Roseneil, Sasha (Nouvelles Questions Féministes, 2011)
L'amitié est un champ d'études peu exploré et cependant d'importance vitale pour les études genre et féministes. En revisitant l'histoire des écrits féministes sur les amitiés entre femmes, l'article explore l'importance qui est donnée à l'amitié par les premières générations de féministes tout au long du XXe siècle. En se concentrant sur les considérations polémiques, théoriques et empiriques à l'égard de l'amitié, l'article suggère que l'amitié a été historiquement fondamentale pour les politiques, les identités et les communautés féministes. Il conclut par un argument en faveur de la place centrale de l'amitié - avec le même sexe, hommes et femmes, mais aussi entre les sexes - dans les programmes de recherche féministes, aujourd'hui et dans l'avenir. Le prisme de l'amitié conduit à une remise en question radicale de l'hétéronormativité des sciences sociales, et attire notre attention sur les façons dont la vie intime a été reconfigurée au début du XXIe siècle.
https://www.jstor.org/stable/41346017 Traduction de : Sasha Roseneil (2006). « Foregrounding Friendship : Feminist Pasts, Feminist Futures ». In Kathy Davis, Mary Evans & Judith Lorber (Éds) Handbook of Gender Women’s Studies, (pp. 322-341). Londres : SAGE Publications.
Keywords: 1900-1999; amitié; approches et analyses; care; cours; cycles supérieurs; discipline; fem7000; genre; histoire de l'art; histoire et politique; hétéronormativité; hétérosexisme; intimité; lesbianisme; littérature française; littérature lesbienne; phi2030; philosophie; premier cycle; périodes historiques; rapports sociaux de sexe; sciences humaines; sexualité; sociologie; systèmes d'oppressions; thématiques; écriture des femmes*; études littéraires

Contested pleasures: The sociopolitical economy of disability and sexuality - Shildrick, Margrit (Sexuality Research & Social Policy, 2007)
Consideration of sexual pleasure in the lives of people with disabilities plays little part in lay consciousness, and practically none in social policy. This article investigates such repression by engaging with a cultural imaginary that fears nonnormative sexuality as being a potential point of societal breakdown. Recent work in disability studies gives a very different understanding of the sexuate body that opens up the parameters of sexuality for everyone. This work challenges current social policy’s supposedly rational utilitarian basis and the principle of equality that together ground a sociopolitical economy of disability predicated on rehabilitation or compensation. Nonetheless, the call for sexual citizenship for people with disabi lities is fraught with difficulties, not least regarding the potential extension of govern mentality. An effective approach not only will take into account the sociopolitical aspects of this issue but also will respond to both the full embodiment of disability and its significance in mainstream culture.
Keywords: EDI; accessibilité; approches et analyses; arts; bioéthique; capacitisme; corps; cours; discipline; intersectionnalité; justice sociale; philosophie; premier cycle; ressource en ligne; sciences; sciences humaines; sex1911; sex1920; sexualité; systèmes d'oppressions; thématiques; études critiques du handicap; études littéraires

King King théorie - Despentes, Virginie (Grasset, 2006)
J'écris de chez les moches, pour les moches, les frigides, les mal baisées, les imbaisables, toutes les exclues du grand marché à la bonne meuf, aussi bien que pour les hommes qui n'ont pas envie d'être protecteurs, ceux qui voudraient l'être mais ne savent pas s'y prendre, ceux qui ne sont pas ambitieux, ni compétitifs, ni bien membrés. Parce que l'idéal de la femme blanche séduisante qu'on nous brandit tout le temps sous le nez, je crois bien qu'il n'existe pas. V.D.
Keywords: 2000 à aujourd'hui; 2000-2009; anticapitalisme; approches et analyses; cours; cycles supérieurs; discipline; discours dominant; europe; fem1000; fem7000; france; hétérosexisme; identités LGBTQIA2+; lit3220; littérature; premier cycle; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; travail; travail du sexe; violences; violences sexistes et sexuelles; études littéraires

Saphisme et décadence dans Paris fin-de-siècle - Albert, Nicole G. (La Martinière, 2005)
Figures emblématiques des années 1900, les saphistes sont associées aux premiers balbutiements d'un féminisme qui dérange et qui, par réaction, nourrit d'inépuisables fantasmes. Objets de scandale ou héroïnes, elles inspirent artistes et poètes. C'est l'ensemble de ces représentations ambiguës qui sont ici analysées.
Keywords: 1800-1899; approches et analyses; arts; corps; discipline; discours dominant; europe; france; lesbianisme; périodes historiques; régions géographiques; sexualité; systèmes d'oppressions; thématiques; études littéraires

Lesbian empire: Radical crosswriting in the Twenties - Wachman, Gay (Rutgers University Press, 2001)
Gay Wachman provides a critical new reading of sexually radical fiction by British women in the years during and after the First World War. She contrasts works by Sylvia Townsend Warner, Virginia Woolf, Rose Allatini, and Evadne Price with more politically and narratively conservative novels by Radclyffe Hall and Clemence Dane. These writers, she states, formed part of an alternative modernist tradition that functioned both within and against the repressive ideology of the British Empire, using fantasy as a means of reshaping and critiquing a world fragmented by war. Wachman places at the center of this tradition Sylvia Townsend Warner's achievement in undermining the inhibitions that faced women writing about forbidden love. She discusses Warner's use of crosswriting to transpose the otherwise unrepresentable lives of invisible lesbians into narratives about gay men, destabilizing the borders of race, class, and gender and challenging the codes of expression on which imperialist patriarchy and capitalism depended.
Keywords: amour interdit; approches et analyses; arts; discipline; europe; littérature; patriarcat; personnes lesbiennes; racisme; royaume-uni; régions géographiques; sexisme; sexualité; systèmes d'oppressions; thématiques; transgression; études littéraires

New sexual agendas - Segal, Lynne (New York University Press, 1997)
"Taking on those who would limit sexual freedom, New Sexual Agendas challenges the notion that there are fixed sexual behaviors for men and women. This engaging collection draws on a number of disciplines including women's studies, literature, gender studies, cultural studies, history, politics, education, sociology, and psychology."
Section: xviii, 278 p
Keywords: LGBTQIA2+; approches et analyses; arts; corps; cours; discipline; histoire; histoire et politique; hétéronormativité; hétérosexisme; hétérosexualité; premier cycle; psychologie; queer; rapports sociaux de sexe; santé; sciences humaines; sexologie; sexualité; soc2014; sociologie; systèmes d'oppressions; thématiques; études de genre; études littéraires

Romance revisited - Pearce, Lynne; Stacey, Jackie (New York University Press, 1995)
Après des décennies de féminisme et de déconstruction, la romance reste fermement ancrée comme une préoccupation centrale dans la vie de la plupart des femmes. Les taux de divorce montent en flèche, la famille traditionnelle est remise en question de toutes parts et pourtant la romance semble indestructible. En termes de représentation culturelle, la popularité de la romance semble également incontestée. La fiction populaire, le cinéma hollywoodien, les feuilletons télévisés et les médias en général affichent tous un appétit apparemment sans limite pour les sujets romantiques. Les pièges de la romance classique – mariages blancs, chansons d’amour, Saint-Valentin – sont plus que jamais commercialement viables. Dans cette anthologie d'essais originaux, la romance est revisitée sous un large éventail de perspectives, non seulement dans la fiction et le cinéma, mais dans toute une gamme de phénomènes culturels. Les essais couvrent des sujets tels que la Saint-Valentin, les relations interraciales, les visions érotiques médiévales et la fiction romantique moderne, la relation entre la poétesse lesbienne HD et Bryher, la blancheur omniprésente du désir romantique, l'érotisme lesbien à l'ère du SIDA et la romance publique de Charles et Diane.
Keywords: anthologie; approches et analyses; arts; classisme; discipline; histoire et politique; outils; ouvrages de références; patriarcat; racisme; romance; sexisme; sexualité; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Sororophobia: Differences among women in literature and culture. - Michie, Helena (Oxford University Press, 1992)
This book looks at how differences among women have been textually represented at a variety of historical moments and in a variety of cultural contexts, including Victorian mainstream fiction, African-American mulatto novels, late twentieth-century lesbian communities, and contemporary country music. Sororophobia designates the complex and shifting relations between women's attempts to identify with other women and their often simultaneous desire to establish and retain difference. Michie argues for the centrality to feminism of a paradigm that moves beyond celebrations of identity and sisterhood to a more nuanced notion of women's relations with other women which may include such uncomfortable concepts as envy, jealousy, and competition as well as more institutionalized ideas of difference such as race and class. Chapters on literature are interspersed by "inter-chapters" on the choreography of sameness and difference among women in popular culture.
Keywords: approches et analyses; arts; classisme; discipline; histoire et politique; littérature; racisme; relations entre femmes*; ressource en ligne; sexualité; systèmes d'oppressions; thématiques; études littéraires

A lure of knowledge: Lesbian sexuality and theory - Roof, Judith (Columbia University Press, 1991)
Lesbianism in literature has been dealt with rather indirectly in the past. Editors have led readers to the "artistry" of a work containing lesbianism, emphasizing instead the literary history and historical context of the work rather than the representations of lesbianism. The editor for Colette's The Pure and the Impure, for instance, affirms that Colette has a knowledge of a "strange sisterhood," but assures readers she has never strayed from the "normal." In the groundbreaking A Lure of Knowledge, Judith Roof demonstrates that representations of lesbian sexuality occupy specific locations or positions in the arguments, subject matter, and rhetoric of Western European and American literary criticism. She examines the political context of representations: how lesbian sexuality is used as a signifier an why it appears when and where it does. Roof argues that attempts to depict or explain lesbian sexuality spur anxieties about knowledge and identity. In reaction to and denial of these anxieties, lesbian sexuality is represented in film, literature, theory, and criticism as foreplay, as simulated heterosexuality, as erotic excess, as joking inauthenticity, as artful compromise, or as masculine mask in a specific repertoire of neutralization and evasion. Challenging the heterosexism of film theory and feminist theory, this book analyzes the rhetorical use of lesbian sexuality. Roof explores a range of discourses, from the woks of such authors as Anais Nin, Olga Broumas, Julia Kristeva, Jane Rule, Luce Iriguray, and Sigmund Freud, to films such as Emmanuelle, Desert Hearts, Entre Nous, and I've Heard the Mermaids Singing, to professional tennis.
Keywords: approches et analyses; arts; cinéma; communication; discipline; hétérosexisme; lesbianisme; personnes lesbiennes; sexualité; sexualité lesbienne; systèmes d'oppressions; thématiques; études culturelles; études littéraires

Lesbian images - Rule, Jane (N.Y., 1975)
Convaincue que l'amour se décrit mieux dans une œuvre d'art, Jane Rule a choisi pour cette étude du lesbianisme le travail d'écrivaines lesbiennes brillamment articulées telles que Gertrude Stein, Colette, Vita Sachville West et Willa Cather. Son souci est de découvrir quelles images des lesbiennes ces écrivaines et d’autres lesbiennes ont dépeintes dans la fiction, la biographie et l’autobiographie – et en particulier comment elles ont été influencées par des concepts religieux et psychologiques ainsi que par leur propre expérience personnelle dans la présentation de leurs personnages lesbiens. En plus de révéler le courage de ces femmes dans un environnement hostile, elle examine la moralité négative de certaines d'entre elles et réévalue leurs idées d'un point de vue féministe. Dans ses chapitres d'introduction, l'auteure examine la manière dont l'amour entre femmes a été perçu par la société depuis l'Antiquité jusqu'à nos jours ; comment l'Église chrétienne a traité l'inversion masculine et féminine comme un péché punissable ; et comment la psychiatrie a évolué à partir des mêmes préjugés anciens qui paralysent l'Église. Ce qui était « péché » est devenu « maladie » et « punition » a été remplacé par « traitement ». Dans son dernier chapitre, Jane Rule examine les changements dramatiques survenus avec l'avènement du mouvement des femmes et les luttes intestines parfois amères et douloureuses entre lesbiennes et féministes – exprimant finalement un sentiment d'espoir et d'optimisme pour un avenir plus positif.
Keywords: approches et analyses; arts; corps; discipline; discours dominant; genre; hétérosexisme; lesbianisme; personnes lesbiennes; relations amoureuses; sexualité; systèmes d'oppressions; thématiques; études littéraires